Association between periodontal condition and subgingival microbiota in women during pregnancy: a longitudinal study - Priscila Viola BORGO; Viviane Aparecida Arenas RODRIGUES; Alfredo Carlos Rodrigues FEITOSA; Karla Correa Barcelos XAVIER; Mario Julio AVILA-CAMPOS (University of São Paulo, 2014)
Objectivo In this study, the gingival conditions and the quantitative detection for Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, Porphyromonas gingivalis and Prevotella intermedia in pregnant women were determined. Material and Methods Quantitative determinations of periodontal bacteria by using a SyBr green system in women during pregnancy were performed. Women at the 2nd and 3rd trimesters of pregnancy and non-pregnant women were included in this study. A. actinomycetemcomitans was observed in high numbers in women at the 2nd and 3rd trimesters of pregnancy with a significant difference (p<0.05). F. nucleatum and P. intermedia were also observed in high levels. Results and Conclusion Our results show that pregnant women are more susceptible to gingivitis, and the presence of A. actinomycetemcomitans in subgingival biofilm might be taken into account for the treatment of periodontal disease.